The Specificity of Afghan Identity in the Context of Globalization - Georgy G. Machitidze (Vestnik RUDN. International Relations)
The article addresses the issue of identifying a Muslim country in the context of globalization, with Afghanistan serving as a case study. For almost 20 years, Western attempts to introduce liberal democratic values into Afghan society have failed. The author highlights the fact that Afghan society has remained wary of elements of globalization for fear of losing its cultural and religious identity. Having established a theocratic regime, the Taliban (recognized as terrorist and banned in Russia) set about restructuring the principles of Afghan nationalism in line with Islamic nationalism. The idea of Islam as a state identity implies that Islam as a comprehensive identity is capable of neutralizing ethnic differences in society. In taking steps to renew the ideological superstructure of the Afghan state, the Taliban (recognized as terrorist and banned in Russia) put forward a new concept termed ‘Talibanism.’ The features and reasons for the shift of the Islamic Emirate of Afghanistan’s leadership away from traditional Deobandism and towards a more acceptable combination of religious-Puritan beliefs adapted to the strict precepts of Islamic law are analyzed. It is concluded that ‘Talibanism’ rejects all forms of republican government and makes a clear distinction between Islamic law and man-made laws, considering the latter to be immoral. The main trend of Kabul’s domestic policy, aimed at re-Islamisation of the insufficiently Islamized Afghan society on a voluntary or coercive basis, is shown. The concept envisages the imposition of a single Islamic identity on Afghan society, accompanied by the violation of women’s rights in employment and education. The rationale behind the Taliban’s (recognized as terrorist and banned in Russia) policy is the belief that Afghan society is degenerating from within and is subject to a process of external destruction that must be stopped. It is observed that the Taliban (recognized as terrorist and banned in Russia) leaders have been influenced in changing their views by their prolonged contacts with representatives of Al-Qaeda (recognized as terrorist and banned in Russia) and other jihadist organizations. The study found that the Taliban (recognized as terrorist and banned in Russia) ideology has acquired some similarities with Salafism, and that the authorities are trying to isolate the Afghan people from the processes of globalization, being ready to protect Islamic values from Western civilization by any means necessary.